Antileishmanial Effects of Acetylene Acetogenins from Seeds of Porcelia macrocarpa (Warm.) R.E. Fries (Annonaceae) and Semisynthetic Derivatives - Ivanildo A. Brito; Fernanda Thevenard; Thais A. Costa-Silva; Samuel S. Oliveira; Rodrigo L. O. R. Cunha; Emerson A. de Oliveira; Patricia Sartorelli; Rafael C. Guadagnin; Maiara M. Romanelli; Andre G. Tempone; João Henrique G. Lago (Molecules, 2022)
As part of our continuous studies involving the prospection of natural products from Brazilian flora aiming at the discovery of prototypes for the development of new antiparasitic drugs, the present study describes the isolation of two natural acetylene acetogenins, (2S,3R,4R)-3-hydroxy-4-methyl-2-(n-eicos-11′-yn-19′-enyl)butanolide (1) and (2S,3R,4R)-3-hydroxy-4-methyl-2-(n-eicos-11′-ynyl)butanolide (2), from the seeds of Porcelia macrocarpa (Warm.) R.E. Fries (Annonaceae). Using an ex-vivo assay, compound 1 showed an IC50 value of 29.9 μM against the intracellular amastigote forms of Leishmania (L.) infantum, whereas compound 2 was inactive. These results suggested that the terminal double bond plays an important role in the activity. This effect was also observed for the semisynthetic acetylated (1a and 2a) and eliminated (1b and 2b) derivatives, since only compounds containing a double bond at C-19 displayed activity, resulting in IC50 values of 43.3 μM (1a) and 23.1 μM (1b). In order to evaluate the effect of the triple bond in the antileishmanial potential, the mixture of compounds 1 + 2 was subjected to catalytic hydrogenation to afford a compound 3 containing a saturated side chain. The antiparasitic assays performed with compound 3, acetylated (3a), and eliminated (3b) derivatives confirmed the lack of activity. Furthermore, an in-silico study using the SwissADME online platform was performed to bioactive compounds 1, 1a, and 1b in order to investigate their physicochemical parameters, pharmacokinetics, and drug-likeness. Despite the reduced effect against amastigote forms of the parasite to the purified compounds, different mixtures of compounds 1 + 2, 1a + 2a, and 1b + 2b were prepared and exhibited IC50 values ranging from 7.9 to 38.4 μM, with no toxicity for NCTC mammalian cells (CC50 > 200 μM). Selectivity indexes to these mixtures ranged from >5.2 to >25.3. The obtained results indicate that seeds of Porcelia macrocarpa are a promising source of interesting prototypes for further modifications aiming at the discovery of new antileishmanial drugs.